2019
DOI: 10.1039/c8tb02763c
|View full text |Cite
|
Sign up to set email alerts
|

Considerations for hydrogel applications to neural bioelectronics

Abstract: Hydrogels have garnered interest as materials in bioelectronics due to the capacity to tailor their properties. Appropriate selection and design of hydrogel systems for this application requires an understanding of the physical, chemical and biological properties as well as their structure–property relationships.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(42 citation statements)
references
References 110 publications
0
42
0
Order By: Relevance
“…Interestingly, PGH 0.1 showed a 30% higher elongation and twice the toughness compared with GH ( Figure 3 d). This was possibly due to multiple networks produced by inter-crosslinking of gelatins and the entanglement between gelatin and PEDOT:PSS chains [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, PGH 0.1 showed a 30% higher elongation and twice the toughness compared with GH ( Figure 3 d). This was possibly due to multiple networks produced by inter-crosslinking of gelatins and the entanglement between gelatin and PEDOT:PSS chains [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…Hydrogels have been employed as 3D constructs which mimic the natural mechanical and structural properties of soft tissue (Khetan and Burdick, 2009;Goding et al, 2019;Syed et al, 2020). A biosynthetic PVA-SG hydrogel construct was chosen as the platform for this study, as it can be tailored to improve outcomes for neural cell encapsulation, as shown in prior research (Goding et al, 2017;Aregueta-Robles et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…[ 12,13 ] The hydrogel layer can function as a window with high water content, permeability to various chemical/biological molecules, and biocompatibility, whereas the elastomer layer serves as a stable and mechanically robust substrate. [ 14–16 ] The hybrid form is useful in demonstrating biochemically functional devices that can stably operate and simultaneously interact with its environment because the small molecules can infiltrate through the hydrogel window. [ 17,18 ] Stretchable electronics, interactive generic circuits, and microfluidic devices that use hybrids have been reported; therefore, the properties of elastomer–hydrogel hybrids can also be useful for interactive soft bioelectronics.…”
Section: Figurementioning
confidence: 99%